REVENUE CHANGES AND EMOTIONAL INTELLIGENCE IN IMPROVING THE PERFORMANCE OF EMPLOYEES CIVIL AREA - Ahmad, Muchtar (Jurnal Aplikasi Manajemen, 2017)
The purpose of this study to determine the effect of acceptance of change and emotional intelligence to improve the performance of civil servants regions (A study in the district was the Regional Secretariat). The study's findings that: (1) Acceptance of the changes have a positive impact on performance and thus increasing the local civil servants, (2) Effect of Emotional Intelligence in improving the performance of local civil servants. The results showed that the acceptance of change positive direct effect on the performance of local government employees the district was Gorontalo Province. The better acceptance of change, the higher the performance of employees, the implication of this research is to increase the performance of employees can be done by improving the relationship between the employer, the environment and employees in the improvement in the acceptance of change. Harmonization within the government formed a situation that can receive favorable changes in governmental organizations district was openly. While civil servants Emotional intelligence is usually measured area of self-awareness of civil servants accountable in its duties and functions in each of its businesses as part of a self-awareness of employees in optimizing their duties in order to reach target. Awareness in building teamwork work and self-management each individual employee will lift the employee performance improvement. But it also still need consistency in enforcing regulatory leadership in maintaining mental stability of employees in working continuously.